Reliability and Validity of the ActivForce Digital Dynamometer in Assessing Shoulder Muscle Force across Different User Experience Levels - Christos Karagiannopoulos; Sean Griech; Brian Leggin (International Journal of Sports Physical Therapy)
# Background